Financial and managerial aspects in human resource management : a practical guide - Pepple, Dennis; Zhang, Crystal (Bingley, U.K. : Emerald Publishing Limited, 2021)
Financial and Managerial Aspects in Human Resource Management: A Practical Guide explores both financial and management accounting and their links to human resource management decisions and practices.The book provides a pedagogic material that examines the fnanicial decisions that are specific to HR practices. Each chapter is mapped to CIPD and SHRM competency models and feature organisational examples, relevant case studies, critical theoretical discussions and end of chapter questions to give readers and learners a critical understanding of the following subjects: Introduction to financial accounting - Income statement and balance sheet - Interpretation of financial statements - Financial ethicsLearning and development cost - Redundancy - Disciplinary and grievance cost - Relocation cost - Family friendly policies - Executive compensation. Written for students and practitioners, this book breaks new ground by being the first to compile the everyday management and ficial decisions of HR managers in a single book. Financial and Managerial Aspects in Human Resource Management is an essential resource for understanding core practical HRM issues in the modern workplace.
Part A. Financial aspects -- Chapter 1. Introduction to financial accounting / Chibuzo Amadi and Amanze Ejiogu -- Chapter 2. Income statement and balance sheet / Dennis Pepple and Chibuzo Ejiogu -- Chapter 3. Interpretation of financial statements / Philip McCosker -- Chapter 4. Financial ethics / O.E Adegbite, O.R Adegbite and A. Y. Ige-Olaobaju -- Part B. Managerial aspects -- Chapter 5. Towards understanding how the HR function relates to the accounting function / Simon Horsman -- Chapter 6. Managing learning and development cost / Joanne Carlier -- Chapter 7. Managing redundancy / Dennis Pepple, Crystal Zhang and Chioma Ofoma -- Chapter 8. Managing disciplinary and grievance cost / Dennis Pepple and Nkem Adeleye -- Chapter 9. Managing relocation costs / Michael Oyelere and Temitope Oyelere -- Chapter 10. Managing family friendly policies / Kehinde Olowookere -- Chapter 11. Executive compensation: transparency, corporate governance and corporate social responsibility perspectives / Chibuzo Ejiogu and Ikedinachi Ogamba.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Personnel management; Business enterprises -- Finance; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management